Personality predicts self-rated health: considering age differences - Kang, Weixi (Frontiers in Psychology, 2023)
Self-rated health (SRH) refers to the subjective evaluation of one’s own health. Big Five personality traits including Neuroticism, Agreeableness, Openness, Conscientiousness, and Extraversion have been consistently found as significant predictors of SRH. In addition, SRH declines with age, and personality traits change with age. Thus, it is reasonable to speculate that age might moderate the associations between personality traits and SRH. The current study analyzed data from 33256 participants with a mean age of 45.78 years old and 55.92% females. The current study found that age significantly moderates the associations between Agreeableness, Openness, and Conscientiousness and SRH after controlling for demographic covariates. The current study implies that personality traits relate to SRH differently at different ages. Thus, studies regarding the associations between personality traits and SRH must take the interactions between age and personality traits into account.